Film Plastics in Manila by Night - David, Joel (Archīum Ateneo, 2024)
As a sample of Third World cinema, Manila by Night (and by association its director, Ishmael Bernal) endured a reputation for technical inadequacy—an ironic assessment, considering its top-rank status in the Philippine film canon. This paper will attempt to revaluate the movie’s aesthetic stature vis-à-vis movements specific to Third Cinema, focusing on ethnographic filmmaking. First will be an analysis of the film’s visual surface, with a consideration of scene selections/limitations/restrictions, the limiting and liberating aspect of night shooting, and the independent-minded spirit which refused to conform to standards of surface polish in filmmaking, as dictated by critics and practitioners. Second will be a consideration of sound, particularly its director’s successful adaptation of the multi-channel recording system to convey overlapping and even simultaneous lines of dialogue. By this means the paper hopes to argue that, contrary to received impressions, Bernal devoted as much aesthetic deliberation to Manila by Night as he did to its justly celebrated narratological and ideological elements.